Analisis Etis-Teonomi Terhadap Frasa “Kecuali Karena Zinah” Teks Matius 19:9 - Harold Pardede (Sekolah Tinggi Teologi Ekumene Jakarta., 2024)
Divorce is one of the things that every Christian family does not want. Especially in the Christian faith, divorce is generally prohibited. However, it is undeniable that there are many cases of divorce among Christian families today. This study aims to provide a different perspective on divorce in the Christian faith according to the text of Matthew 19:9. By using qualitative methods and contextual analysis of the text of Matthew 19:9, this study wants to look at divorce due to adultery. The analysis of the text of Matthew 19:9 is also linked to the understanding of theonomic ethics so that divorce can be done if there is indeed a problem of adultery in the Christian family. With a theonomic ethics approach that emphasizes freedom in human responsibility and how to side with victims, divorce in Christian families can be done, because God's will is not alien to the fulfillment of our humanity. So through this study, Christian families who are having marital problems are still able to see God's infinite love for the limited human ability or flesh.